ABO blood group and von Willebrand factor: biological implications - Franchini, Massimo; Crestani, Silvia; Frattini, Francesco; Sissa, Cinzia; Bonfanti, Carlo (Clinical chemistry and laboratory medicine, 2014)
ABO blood group antigens are complex carbohydrate molecules expressed on the surface of red blood cells and a variety of human cells and tissues. It is well known that ABO blood type exerts a profound influence on hemostasis, being a major determinant of von Willebrand factor (VWF), and consequently factor VIII, plasma levels. In this review, we will focus on the molecular mechanisms underlying the interaction between ABO blood group and VWF in normal and pathological conditions.